'Sweeping rods': cargo transport by self-propelled bimetallic microrods moving perpendicular to their long axis. Issue 9 (19th February 2021) - Arslanova, Alina; Dugyala, Venkateshwar Rao; Reichel, Erwin Konrad; Reddy, Naveen; Fransaer, Jan; Clasen, Christian
Abstract : We report for the first time on a much more effective one-by-one microscopic cargo collection and transport by sideways propelled Janus cylinders, which eventually results in pyramidical shaped micro-rod-cargo aggregates. Abstract : A possible application of self-propelling particles is the transport of microscopic cargo. Maximizing the collection and transport efficiency of particulate matter requires the area swept by the moving particle to be as large as possible. One such particle geometry are rods propelled perpendicular to their long axis, that act as "sweepers" for collecting particles. Here we report on the required Janus coating to achieve such motion, and on the dynamics of the collection and transport of microscopic cargo by sideways propelled Janus rods.